Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1269/jrr.48.a15
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation System for HIMAC

Abstract: Clinical trials of carbon radiotherapy started at HIMAC in 1994 using three treatment rooms and four beam ports, two horizontal and two vertical. The broad beam method was adopted to make a three-dimensionally uniform field at an isocenter. A spot beam extracted from an accelerator was laterally spread out by using a pair of wobbler magnets and a scatterer. A bar ridge filter modulated the beam energy to obtain the spread out Bragg peak (SOBP). The SOBP was designed to be flat in terms of the biological dose b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 26 publications
0
82
0
Order By: Relevance
“…The facility and broad beam irradiation procedure has been described elsewhere (Kanai et al 1999;Torikoshi et al 2007). Cells were irradiated in either T25 flasks or microscopy flasks (Nunc, New York, USA) at a confluency of about 80%.…”
Section: Carbon Ion Irradiationmentioning
confidence: 99%
“…The facility and broad beam irradiation procedure has been described elsewhere (Kanai et al 1999;Torikoshi et al 2007). Cells were irradiated in either T25 flasks or microscopy flasks (Nunc, New York, USA) at a confluency of about 80%.…”
Section: Carbon Ion Irradiationmentioning
confidence: 99%
“…MLC-based collimation solves many of the issues with aperture-based collimation by shaping the lateral extent of the beam separately for each energy layer, as implemented with the layer stacking technique. 9 The delivery may be automated, and the need for patient-specific hardware is eliminated. Bues et al 8 have investigated the use of MLC based spot scanning and found that the lateral penumbra was improved for beams with an energy less than 159 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…The new treatment facility was constructed as an extension of the existing treatment building and shared the accelerator with it 5 , 6 . The goal of the new facility was to provide carbon ion beam scanning irradiation with respiratory gating.…”
Section: Methodsmentioning
confidence: 99%